Ударостійкий чавун для молольних тіл - Ломакін, В. М.; Молокост, Л. А.; Lomakin, V.; Molokost, L.; Ломакин, В. Н. (ЦНТУ, 2020)
Проведено дослідження динамічної міцності (ударостійкості) молольних тіл, відлитих з низькохромистого чавуну в багатомісному кокілі, в залежності від вмісту хрому в сплаві. Встановлено підвищення ударостійкості виливків куль при збільшенні масової частки хрому в чавуні в межах до 1%. При цьому найбільше зростання динамічної міцності спостерігається при збільшенні масової частки хрому від 0,3% до 0,5%. При подальшому зростанні вмісту хрому ударостійкість білого низьколегованого чавуну підвищується менш помітно і при вмісту хрому 0,7-0,8% досягає максимуму. A study of the dynamic strength (impact resistance) of grinding bodies cast from low-chromium cast iron in a multi-seat chill mold depending on the chromium content in the alloy is carried out. As a starting point, cast iron of the following composition was used: carbon – 3,0%, silicon – 1,6%, manganese – 0,4%, sulfur – 0,05%, phosphorus – 0,06%. For the study, several batches of balls with a diameter of 60 mm were cast with different chromium content in cast iron, from 0 to 1%. Cast iron was smelted in a mediumfrequency induction furnace, such as IChT, with the main lining on a charge of pure pig iron and steel low-carbon scrap. The temperature of cast iron production was 1500 °C. Liquid cast iron was subjected to alloying with medium carbon ferrochrome. Balls were cast in multi-seat chill molds. When tested for impact resistance, the grinding ball received a striking blow of mass 50 kg, falling from a height of 0,5 m. The frequency of application of dynamic loads was 10 beats per minute. Impact resistance was determined by the average number of impacts sustained by the grinding body prior to destruction. An increase in the impact resistance of ball castings has been established with an increase in the mass fraction of chromium in cast iron up to 1%. Moreover, the greatest increase in dynamic strength is observed with an increase in the mass fraction of chromium from 0,3% to 0,5%. With a further increase in the chromium content, the impact resistance of white low-alloy cast iron increases less noticeably, and in the presence of chromium 0,7-0,8% reaches a maximum. The difference in hardness from the surface (~ 52 HRC) to the center of the ball (~ 42 HRC) is a value of about 10 units. The established impact resistance of grinding bodies made it possible to conclude: when grinding solid rocks with high content of solid quartz, the use of low chromium cast iron as a material for grinding media is the most effective, as in terms of achieve high impact resistance, and to ensure cost-effective performance. Проведено исследование динамической прочности (ударостойкости) мелющих тел, отлитых из низкохромистого чугуна в многоместном кокиле, в зависимости от содержания хрома в сплаве. Установлено повышение ударостойкости отливок шаров при увеличении массовой доли хрома в чугуне в пределах до 1%. При этом наибольший рост динамической прочности наблюдается при увеличении массовой доли хрома от 0,3% до 0,5%. При дальнейшем росте содержания хрома ударостойкость белого низколегированного чугуна повышается менее заметно, и при наличии хрома 0,7-0,8% достигает максимума.
Impact Resistant Cast iron for Grinding Bodies
Ударостойкий чугун для мелющих тел
Keywords: чавун; розплав; куля; кокіль; легування; хром; ударостійкість; cast iron; melt; ball; chill mold; alloying; chrome; impact resistance; чугун; расплав; шар; кокиль; легирование; ударостойкость